Extending the fossil record of late Oligocene non-biting midges (Chironomidae, Diptera) of New Zealand - Baranov, Viktor; Hammel, Jörg U.; Lee, Daphne E.; Schmidt, Alexander R.; Kaulfuss, Uwe (PeerJ, Inc., 2025)
BackgroundThe modern chironomid fauna of New Zealand is diverse, highly endemic and reflects a complex biogeographical history. This fauna has been important for developing phylogenetic and biogeographic concepts including Brundin’s writings on transantarctic relationships but until now the fossil record to support these reconstructions has been very limited. Here we describe the first fossil species of Chironomidae, subfamily Orthocladiinae, from New Zealand, based on inclusions in amber from the late Oligocene Pomahaka Formation of the South Island.MethodsWe examined newly excavated fossil tree resin (amber) from the late Oligocene Pomahaka Formation in southern New Zealand for inclusions. Amber pieces containing chironomids were prepared and morphologically investigated using light-microscopy and µCT-scanning. Specimens were taxonomically evaluated using identification keys for modern adult chironomid midges. Habitus and key morphological features of each specimen were documented photographically and/or by line drawings.ResultsThirteen Chironomidae specimens from Pomahaka amber were identified as members of the subfamily Orthocladiinae Kieffer. Bryophaenocladius zealandiae sp. nov. Baranov is the first Southern Hemisphere fossil of the genus. Bryophaenocladius Thienemann, 1934 is absent from the extant fauna of the main islands of New Zealand; however, it may be present on the subantarctic Auckland Islands. Two incompletely preserved specimens are described as Morphotype 1 cf. Bryophaenocladius zealandiae. Based on a male adult, Pterosis extinctus sp. nov. Baranov is described as the first fossil record of the extant genus Pterosis Sublette and Wirth, today represented by a single endemic species on the New Zealand subantarctic Auckland Islands and Campbell Island. Two female adult specimens are described as Morphotype 2 cf. Metriocnemini. The new fossils of the genera Bryophaenocladius and Pterosis belong to chironomid taxa requiring terrestrial or semi-aquatic habitats for larval development, supporting the ...